2007
DOI: 10.1175/jas4028.1
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Predictability of Moist Baroclinic Waves: Convection-Permitting Experiments and Multistage Error Growth Dynamics

Abstract: A recent study examined the predictability of an idealized baroclinic wave amplifying in a conditionally unstable atmosphere through numerical simulations with parameterized moist convection. It was demonstrated that with the effect of moisture included, the error starting from small random noise is characterized by upscale growth in the short-term (0-36 h) forecast of a growing synoptic-scale disturbance. The current study seeks to explore further the mesoscale error-growth dynamics in idealized moist barocli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
245
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 238 publications
(273 citation statements)
references
References 27 publications
28
245
0
Order By: Relevance
“…Among others, much attention has been paid to skillful NWP for severe weather (e.g., Kain et al 2006, Hohenegger andSchär 2007a, b;Kawabata et al 2007;Roberts and Lean 2008). Recently, the ensemble Kalman filter (EnKF; Evensen 1994Evensen , 2003 has become a major method in data assimilation (DA), and has contributed to investigate convection-permitting regional NWP (e.g., Zhang et al 2007;Stensrud et al 2009Stensrud et al , 2013Clark et al 2010;Schwartz et al 2010;Baldauf et al 2011;Melhauser and Zhang 2012;Yussolf et al 2013, Kunii 2014a, Weng and Zhang 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, much attention has been paid to skillful NWP for severe weather (e.g., Kain et al 2006, Hohenegger andSchär 2007a, b;Kawabata et al 2007;Roberts and Lean 2008). Recently, the ensemble Kalman filter (EnKF; Evensen 1994Evensen , 2003 has become a major method in data assimilation (DA), and has contributed to investigate convection-permitting regional NWP (e.g., Zhang et al 2007;Stensrud et al 2009Stensrud et al , 2013Clark et al 2010;Schwartz et al 2010;Baldauf et al 2011;Melhauser and Zhang 2012;Yussolf et al 2013, Kunii 2014a, Weng and Zhang 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, much attention has been paid to skillful NWP for severe weather (e.g., Kain et al 2006, Hohenegger and Schär 2007a, b;Kawabata et al 2007;Roberts and Lean 2008). Recently, the ensemble Kalman filter (EnKF;Evensen 1994Evensen , 2003 has become a major method in data assimilation (DA), and has contributed to investigate convection-permitting regional NWP (e.g., Zhang et al 2007;Stensrud et al 2009Stensrud et al , 2013Clark et al 2010;Schwartz et al 2010; Baldauf et al 2011;Melhauser and Zhang 2012; Yussolf et al 2013, Kunii 2014a, Weng and Zhang 2016.Recently, Miyoshi et al (2016aMiyoshi et al ( , 2016b reported an innovation of the "Big Data Assimilation" (BDA) technology, implementing a 30-second-update, 100-m-mesh local ensemble transform Kalman filter (LETKF;Hunt et al 2007) to assimilate data from a Phased Array Weather Radar (PAWR) at Osaka University (Ushio et al 2014) into regional NWP models known as the Japan Meteorological Agency non-hydrostatic model (JMA-NHM, Saito et al 2006Saito et al , 2007 and the Scalable Computing for Advanced Library and Environment-Regional Model (SCALE-RM, Nishizawa et al 2015). The PAWR captures the rapid development of convective activities every 30 seconds at approximately 100-m resolution.…”
mentioning
confidence: 99%
“…However, the appropriate use and interpretation of convective-scale forecasts is a difficult issue, not least because there is currently only a limited understanding of predictability at such scales. The baroclinic wave simulations by Zhang et al (2003Zhang et al ( , 2007 provide a good example of the different (faster) character of error growth with explicitly modelled as opposed to parametrized deep convection. Stronger nonlinearities and faster error growth at convective scales imply that ensemble strategies may be particularly useful at such scales, as argued by various authors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the overall strong performance of F nc is owed to an ability of random perturbations to tap into important moist convective dynamics. This notion originates from the work of Zhang (2005) and Zhang et al (2007), who found that random perturbations can give rise to considerable ensemble variance through a multistage process that is governed initially by small-scale moist convection and later by large-scale baroclinic dynamics. Reinforcing this notion is the fact that F nc performed best in the tropics, a region where moist convective processes predominate.…”
Section: Discussionmentioning
confidence: 99%